Dualisme Pasar dan Ketimpangan Distribusi Pendapatan dalam Pembangunan Ekonomi Lokal di Kecamatan Kraksaan - Junaedi, Deddy; Fitryningtyas, Cahya; Ali, Dela Nafisyah; Fatimah, Dian; Putri, Dwivo Monica Risqi; Rosanti, Nur Mauliddyah; Wardani, Risma (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
Local economic development in Kraksaan District has shown an increase in economic activities over recent years. This growth can be observed through the rising number of economic actors and the expansion of market activities at the local level. However, this increase in economic activity has not been accompanied by equitable income distribution among community groups. This condition indicates that economic progress in the district has not been evenly enjoyed by all segments of society. This study aims to analyze market dualism and its impact on income distribution inequality from a market segmentation perspective. The research employs a qualitative descriptive method using in-depth interviews, field observations, and document analysis of secondary data, including statistics from the Central Bureau of Statistics of Probolinggo Regency in 2024. The data indicate that the poverty rate in Kraksaan District reached approximately 16.31 percent, reflecting disparities in economic capacity among social groups. The findings reveal segmentation between economic actors connected to modern markets and those operating within traditional markets. Actors with access to modern markets experience more stable incomes, while traditional actors rely on daily and uncertain earnings. Unequal access to capital, technology, and market networks widens income gaps and shows that development benefits are unevenly distributed.